Parental Awareness and Response to Cyberbullying: A Qualitative Study of Nigerian Parents - Iloakasia, Adaobi Jennifer; Obumse, Nneka Anthonia (Jurnal Kajian Bimbingan dan Konseling, 2026)
The problem of cyberbullying has been gaining momentum in modern society because of the dynamic development of digital technologies and the extensive use of social media by adolescents. This paper thus examined the parental cognition and reaction to cyberbullying of Nigerian parents with a particular emphasis on Anambra State. The research design in the study was a qualitative one, based on a phenomenological approach to reflect the experiences of parents. Purposive selection of parents with children in secondary schools was done (30 parents). The collection of data was done via semi-structured interviews, and thematic analysis was used to analyze the data and determine patterns and themes that were recurring. Results showed that parental awareness of cyberbullying was skewed with some parents having high to low levels of understanding of cyberbullying. Most parents used informal sources of information like social media, children and peer discussions. Even though the majority of the participants were aware of cyberbullying as a negative factor that adversely affects the emotional and psychological health of adolescents, some of them still did not consider it as a serious issue in relation to physical bullying. Responses by the parents were in the form of counseling, limiting use of the devices, monitoring, and reporting to the schools, but these were usually hampered by the lack of digital literacy, secrecy by children, and insufficient organizational support. The paper concludes that parents have a growing awareness of cyberbullying but there are still critical areas of knowledge and effective intervention techniques.